Abundance of land, shortage of housing - Kristian Niemietz (Institute of Economic Affairs (IEA), 2012)
Government's timid reform will not solve chronic housing affordability problemsNot enough is being done to reduce the extraordinarily high cost of housing in Britain. This is the finding of a new report released today by the Institute of Economic Affairs Abundance of land, shortage of housing.In the research Kristian Niemietz looks at how housing costs in the UK have exploded in recent decades. Real-terms house prices in 2011 were more than two-and-a-half-times higher than in 1975, with rent levels following suit. Nothing about this was inevitable. Many other countries have experienced rising housing costs as well, but in most other cases, the increase has been much lower and/or largely transitory. In the USA, Germany and Switzerland, real-terms house prices are still close to their 1975 levels.Other main findings include:· Housing affordability measures show housing to be unaffordable in every single one of the 33 regions in the UK.· There is still plenty of room for development in the UK:· Only 1/10th of England's surface land is developed and even in developed areas, the single biggest item is gardens.· Literally 'concreted-over' land makes up only 1/20th of England's surface area.· Housing benefit is a flawed approach to dealing with the problem of low-cost housing - it favours those living in expensive areas rather than those on low incomes.· The main difference between the UK and its north-western European neighbours is not in demographics, but in completion rates of new dwellings.· Empirical evidence from around the world shows that planning restrictions are the key determinant of housing costs.Recommendations· Only a thorough liberalisation of the planning system can address the affordability crisis.· The government must resist vested interests lobbying against planning reform to help those struggling to afford to buy a home.· The government's National Planning Policy Framework does not address the fundamental flaw in the current planning framework - that the current incentives encourage NIMBYism.· The combination of a restrictive planning system and an over-centralised tax system should be addressed so that local residents obtain the advantages of development.· It must enable rational trade-offs between preserving valuable pieces of countryside and other considerations:· One way to achieve this is to extend the coalition's 'localism' agenda to local finances and planning. If local authorities had to cover most of their expenditure through local taxes, they would have an interest in enlarging their tax base, and granting planning permission would be one way of doing so. People would be free to vote for NIMBY policies, but they would be aware of the cost. Blocking development would mean foregoing tax cuts or better local public services.
Keywords: 330; Population density; Social housing policy; Speculation; Real estate price; Great Britain; Bevölkerungsdichte; Soziale Wohnungspolitik; Spekulation; Immobilienpreis; Großbritannien